2013
DOI: 10.1177/0897190012466897
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Care for Patients Undergoing S-1 Plus Cisplatin Therapy for Unresectable Recurrent Gastric Cancer

Abstract: We examined the adverse gastrointestinal events associated with tegafur/gimeracil/oteracil potassium (S-1) plus cisplatin therapy for unresectable recurrent gastric cancer and risk factors for discontinuing therapy due to adverse events. A total of 65 subjects who had received S-1 plus cisplatin therapy for gastric cancer at Ogaki Municipal Hospital were examined. We found that the risk factors for discontinuation of the therapy due to adverse events were serum albumin (Alb) level less than 3.5 g/dL (odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…However, during second-line therapy with S-1, the frequency of grade ≥2 fatigue and gastrointestinal toxicity was 27.0% (10̸37 cases) in patients with Alb levels <3.5 g̸dl. This result is similar to that of previous studies (15,16) and should be considered when treating patients with S-1, as it may affect the treatment course. Similarly, fatigue and gastrointestinal toxicity in APC chemotherapy patients with Alb levels <3.5 g̸dl must be carefully considered when planning the chemotherapy protocol.…”
Section: Patients Who Received Patients Who Did Not Receive Second-lisupporting
confidence: 82%
See 1 more Smart Citation
“…However, during second-line therapy with S-1, the frequency of grade ≥2 fatigue and gastrointestinal toxicity was 27.0% (10̸37 cases) in patients with Alb levels <3.5 g̸dl. This result is similar to that of previous studies (15,16) and should be considered when treating patients with S-1, as it may affect the treatment course. Similarly, fatigue and gastrointestinal toxicity in APC chemotherapy patients with Alb levels <3.5 g̸dl must be carefully considered when planning the chemotherapy protocol.…”
Section: Patients Who Received Patients Who Did Not Receive Second-lisupporting
confidence: 82%
“…The frequency of AEs and treatment continuity associated with second-line S-1 chemotherapy have not been extensively investigated (11)(12)(13)(14). We previously reported that albumin (Alb) levels <3.5 g̸dl and creatinine clearance levels <78 ml̸min were risk factors for treatment discontinuation or dosage reduction of S-1 in gastric cancer chemotherapy (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the dosage and duration of S-1 treatment may influence patient prognosis, suggesting that medication adherence and continuity of treatment are crucial. However, S-1 continuation is sometimes challenging due to adverse events (AEs) such as leukopenia, neutropenia, anorexia, nausea, vomiting, diarrhea and stomatitis (2)(3)(4). In particular, AEs such as malaise and anorexia may reduce patient quality of life (QOL), which may significantly reduce medication adherence, leading to subsequent medication rejection (4).…”
Section: Introductionmentioning
confidence: 99%